Practicing Strategy : Text and cases - Paroutis, Sotirios (SAGE Publications, Ltd. (UK), 2016)
Shortlisted for the 2013 Chartered Management Institute textbook award Practicing Strategy broke new ground when it first published by focusing on the strategy-as-practice approach, which considers strategy not only as something an organisation has but something which its members do. The new edition deals with a selection of topics that have been central in recent academic debates in the strategy-as-practice area and includes 7 New chapters on topics such as Chief Executive Officers, Middle Managers, Strategic Alignment and Strategic Ambidexterity in line with developments in the field New case studies throughout including Narayana health, the turnaround of Reliant group and relocating a business school Tutor and student access to online resources inlcude additional readings, an Instructor′s Manual, PowerPoint slides, author podcasts and videos. Aimed at undergraduate and postgraduate students taking advanced strategy modules and practitioners alike.